Changes in anamnestic data of patients waiting for dental surgery in Hungary in the past 10 years - Csaba Lászlófy; Sándor Bogdán; Nóra Magyar; Attila Szűcs; Liza Pelyhe; Zsolt Németh (Hungarian Dental Association, 2024)
All dental treatments and dental surgeries are preceded by taking a medical history. Our experience shows that in the last decade the number of anamnestic data that we have to take into account during our treatments has multiplied. Because the majority of our patients comes from an ageing society, and the drugs receiving for the treatment of their illnesses have become multifaceted and the protocol for their use often changes. We investigated these trends in our researches.